THE DIAGNOSTIC ACCURACY OF NUMERICAL COMPUTED TOMOGRAPHY SEVERITY INDEX AND RANSON SCORE IN PREDICTING SEVERE ACUTE PANCREATITIS - Shah, Rahmat Ullah; Shah, Sadia; Ahmad, Shabir (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the diagnostic accuracy of numerical CT severity index (CTSI) and Ranson score in predicting severe Acute Pancreatitis (AP) keeping organ failure as the gold standard. Methodology: This descriptive cross-sectional study was carried out in the Department of Surgery, Medical Teaching Institute, Lady Reading Hospital Peshawar, from November 2020 to May 2021 on 238 patients with acute pancreatitis. All patients were subjected to the prediction of Severe Acute Pancreatitis (SAP)/organ failure on CTSI and Ranson criteria. Results: The mean age of the participants was 30.7+7.6 years. There were 54.2% male and 45.8% female as per gender distribution. The mean duration of AP at presentation was 3.8 +1.8 days. Prediction of SAP in terms of organ failure was predicted in 55.9% of patients on Ranson criteria and 59.2% of patients on CTSI. The sensitivity of Ranson criteria was 37.5% and specificity of 25.4% with a Positive Predictive Value (PPV) of 33.8% and a Negative Predictive Value (NPV) of 28.5%. The sensitivity of CTSI was 88.9% and specificity 71.1% with PPV of 75.9% & NPV of 86.6%. Conclusion: CTSI is a highly sensitive and specific tool for predicting the severity of acute pancreatitis when compared to the Ranson criteria in patients presenting with acute pancreatitis.